Elemental composition analysis of stony meteorites discovered in Phitsanulok, Thailand - T. Loylip (2018)
© Published under licence by IOP Publishing Ltd. A meteorite is a fragment of pure stone, iron or the mixture of stony-iron. The falling of meteorites into Earth's surface is part of Earth's accretion process from dust and rocks in our solar system. When these fragments come close enough to the Earth to be attracted by its gravity, they may fall into the Earth. Following the detection of objects that fall from the sky onto a home in Phitsanulok in June 27, the meteorites were analyzed by scanning electron microscopy coupled with energy dispersive X-ray spectroscopy (SEM/EDS) instruments. The results from SEM/EDS analysis show that the meteorites are mainly composed of Fe-Ni and Fe-s. The meteorite is Achondrite, a class of meteorite which does not contain Chondrule. The meteorites in this work are thought to be part of a large asteroid.